2011
DOI: 10.1016/j.lwt.2010.08.015
|View full text |Cite
|
Sign up to set email alerts
|

Enzymatic properties of transglutaminase produced by a new strain of Bacillus circulans BL32 and its action over food proteins

Abstract: a b s t r a c tThe aim of this study was to physicochemically characterize transglutaminase (TGase) from Bacillus circulans BL32, a strain recently isolated from the Amazon basin region, for its application in food systems. The effects of pH and temperature on the enzyme activity were determined by Central Composite Rotatable Design (CCRD), with maximal TGase activities obtained for pH between 5.7 and 8.7 and temperatures of 25e45 C. This microbial TGase showed to be remarkably stable: over 90% of its activity… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(4 citation statements)
references
References 40 publications
0
3
0
1
Order By: Relevance
“…As a relatively new enzyme in baking, TGM catalyses the reaction between an εamino group on protein-bound glutamine residues leading to covalent crosslinking of protein (Motoki and Seguro 1998;Renzetti et al 2008;Renzetti et al 2012;Volken de Souza et al 2011;Zhu and Tramper 2008). During enzymatic catalyzed reaction of polymers, polymers undergo mainly two chemical reactions; being that polymers can be degraded to smaller fractions and amino acids (de-polymerization) or they can crosslink directly with protein residues (polymerization) to form high molecular weight polymers.…”
Section: Resultsmentioning
confidence: 99%
“…As a relatively new enzyme in baking, TGM catalyses the reaction between an εamino group on protein-bound glutamine residues leading to covalent crosslinking of protein (Motoki and Seguro 1998;Renzetti et al 2008;Renzetti et al 2012;Volken de Souza et al 2011;Zhu and Tramper 2008). During enzymatic catalyzed reaction of polymers, polymers undergo mainly two chemical reactions; being that polymers can be degraded to smaller fractions and amino acids (de-polymerization) or they can crosslink directly with protein residues (polymerization) to form high molecular weight polymers.…”
Section: Resultsmentioning
confidence: 99%
“…The microbial transglutaminase (MTG) is widely used in the food industry to improve the texture and nutrition [4, 5]. Besides, TG has broad potential applications in biopharmaceuticals [69],tissue engineering [3, 7], site-directed protein cross-linking [1, 3, 10], and antibody-drug conjugates [11].…”
Section: Introductionmentioning
confidence: 99%
“…TGase from walleye pollack, fish for surimi, has been purified and characterized by Kumazawa et al [ 26 ]. Otherwise, many researchers have shown that TGase can be used in the processing of dairy, wheat and soybean products in order to improve texture, water-holding capacity, elasticity, nutritional value and appearance [ 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 ].…”
Section: Introductionmentioning
confidence: 99%